Relationship of Breast Care with Milk Smoothness in Postpartum Mothers in The Work Area of Primary Health Care Kaliwates, Jember - Aurellia, Regina; Subiastutik, Eni; Palupi, Jenie (Universitas Bondowoso, 2024)
Background: Increased exclusive breastfeeding is important in an effort to improve the health of babies and mothers. But in reality, it's still a lot found in society that mothers who don't want to breastfeed their children because their breast milk is not smooth. Based on data from the Jember District Health Service in 2022 for the month of November shows that of the 49 Primary Health Care Kaliwates are in the last place with an exclusive breast milk achievement of 2.6% of the target of 100%. The aim of this study is to find out the relationship between breast care and milk smoothness in postpartum mothers in the work area of Primary Health Care Kaliwates. Method: Design research using Pre Experimental Design with One Group Pretest - Posttest. A population of 40 mothers breathed with a sample of 36. Sampling was conducted in three regions namely kaliwates, big tiganes and grand gardens with a random sampling cluster of 15 posyandu. Results: Breast care 11(61.1%), breast care 7(38.9%). Baby weight gain 14(77.8%), baby weight gain 4 (22.2%). Chi Square test analysis value with a p-value of 0.028 < α 0.05 which means there is a relationship between breast care and post-partum milk smoothness in the Primary Health Care Kaliwates. Postpartum mothers who do proper breast care and do it regularly can help launch breast milk and also increase baby weight gain. Conclusion: The more regularly you do breast care, the more smoothly your milk is produced.